2020
DOI: 10.1590/1518-8345.3198.3230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tobacco, alcohol consumption, eating habits and physical activity in nursing students

Abstract: Objective: to determine the consumption of alcohol, tobacco, eating habits, and physical activity among nursing students and to detect whether being a nursing student is a protective factor against these habits. Method: a questionnaire was used to collect information on age, academic year, sex, alcohol and tobacco consumption, physical activity, and healthy eating. An information sheet and informed consent form were given. The sample was composed of 264 students aged between 18-30 years from four academic yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 45 publications
0
16
0
14
Order By: Relevance
“…Another study also identified higher use of tobacco and illicit drugs among university students in the Humanities (23) . It is noteworthy, however, that although Health Sciences courses have greater access to information, less alcohol use was identified among Exact/Earth Sciences and Linguistics/Literatures/Arts courses, and less use of illicit drugs among Engineering and Exact/Earth Sciences courses, showing that not only access to theoretical content would favor their choices (as also demonstrated in another study) (24) .…”
Section: Discussionmentioning
confidence: 57%
“…Another study also identified higher use of tobacco and illicit drugs among university students in the Humanities (23) . It is noteworthy, however, that although Health Sciences courses have greater access to information, less alcohol use was identified among Exact/Earth Sciences and Linguistics/Literatures/Arts courses, and less use of illicit drugs among Engineering and Exact/Earth Sciences courses, showing that not only access to theoretical content would favor their choices (as also demonstrated in another study) (24) .…”
Section: Discussionmentioning
confidence: 57%
“…Respecto al semestre, Tovar et al 38 en estudiantes de Medicina, Tamayo et al 39 en estudiantes de Odontología y Rodríguez et al 40 En cuanto al estudio, esta investigación fue de tipo transversal, participaron programas de una sola universidad y se involucraron estudiantes de los semestres I a IV, impidiendo conocer si las diferencias descritas pueden ocurrir en otros programas y/o en semestres más avanzados de cada programa. Sin embargo, una fortaleza de esta investigación es el tamaño de la muestra (se evaluaron aproximadamente 1 de cada 2 estudiantes, 54% de la población), lo que permitió obtener mejor precisión en los hallazgos.…”
Section: Discussionunclassified
“…Esses índices se aproximam de uma pesquisa realizada na região sul do Brasil, envolvendo 12 cursos da área da saúde que encontrou, respectivamente, prevalências de 85% e 56,1% (19) . Populações semelhantes em outras regiões do país e da América Latina apresentaram prevalência aproximada de consumo (74,9%) (20) , (83,7%) (7) , (85%) (21) e (86%) (22) .…”
Section: Discussionunclassified
“…Nesse sentido, explora-se o questionamento acerca da vida universitária atuar como fator de proteção ou de risco para o uso de álcool e outras drogas (4)(5)(7)(8)(9) , uma vez que vêm sendo utilizadas pelos estudantes também como estratégia de lazer (10) .…”
unclassified
See 1 more Smart Citation